2004
DOI: 10.1111/j.1472-765x.2004.01474.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of Lactobacillus johnsonii FI9785 for use as a defined competitive exclusion agent against bacterial pathogens in poultry

Abstract: Aims: To test the efficacy of Lactobacillus johnsonii FI9785 in reducing the colonization and shedding of Salmonella enterica serotype Enteritidis, Escherichia coli O78:K80 and Clostridium perfringens in poultry. Methods and Results: Specific pathogen-free chicks (1 day old) were dosed with a single oral inoculum of 1 · 10 9 CFU. Lactobacillus johnsonii FI9785 and 24 h later were challenged in separate experiments with S. Enteritidis (S1400, nal r ) and E. coli O78:K80 (EC34195, nal r ). There were no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 32 publications
2
120
0
6
Order By: Relevance
“…In similar case, Murry et al (2006) found lower Coliforms bacteria count in birds by feeding probiotics. Therefore, the beneficial microorganisms establish in the digestive tract and prevent the pathogens (Tellez et al, 2001;La Ragione et al, 2004). Also, in our experiment, Bifidobacterium count was higher at whole period (1 to 42 days).…”
Section: Resultsmentioning
confidence: 49%
“…In similar case, Murry et al (2006) found lower Coliforms bacteria count in birds by feeding probiotics. Therefore, the beneficial microorganisms establish in the digestive tract and prevent the pathogens (Tellez et al, 2001;La Ragione et al, 2004). Also, in our experiment, Bifidobacterium count was higher at whole period (1 to 42 days).…”
Section: Resultsmentioning
confidence: 49%
“…La Ragione & Woodward (2003) verified that the administration of viable spores of Bacillus subtilis to birds free from specific pathogens challenged with C. perfringens reduced the number of pathogens in the spleen, duodenum, colon and cecum, reporting similar results with a probiotic based on Lactobacillus johnsonii (La Ragione et al, 2004). Haghighi et al (2006) shown that a commercial probiotic containing Lactobacillus acidophilus, Bifidobacterium bifidum, and Streptococcus faecalis stimulated the production of antitoxin α IgA from C. perfringens in the intestine of non-vaccinated chicks.…”
Section: Exclusion Of Pathogens and Immunitymentioning
confidence: 53%
“…또한 Lactobacillus는 Campylobacter (Ghareeb et al, 2012;Neal-McKinney et al, 2012), Clostridium (La Ragione et al, 2004) 및 Salmonella (Chen et al, 2012;Ghareeb et al, 2012) 군집을 감소시켜 가금 식품 안전성을 높인다.…”
unclassified